THE USE OF YOUTUBE VIDEO FOR LEARNING ENGLISH AT SENIOR HIGH SCHOOL - Sapnur, Aisyah; Weda, Sukardi; Abduh, Amirullah (Universitas Negeri Makassar, 2023)
This study investigated the use of YouTube video for learning English at senior high school. It aimed to find out how do the students use YouTube for speaking skills at senior high school and what are the student’s perception on the use of YouTube video in learning speaking. This study employed a qualitative method. In this study used purposive sampling to collect the data. Research instrument was used is interview. Findings shows that the students use YouTube video for speaking skill activities in daily life they use in their home and sometimes in school and there is the student download the video and watched everywhere with they own handphone, laptop and tv. The students learning English around 3 minutes until 2 hours in a day. And also show that students can have a positive perception of using YouTube to improve their speaking skills based on their responses to the interview session.